Real, Reel and the Anthropocene: Eco-trauma Testimonies in the Film Valiya Chirakulla Pakshikal - Bibin Thomas; Reju George Mathew (CINEJ Cinema Journal, 2021)
The paper attempts to read the Endosulfan disaster in Kerala as an instance of the Anthropocene wherein the unscientific use of a pesticide resulted in the persistent misery of a population and the ecology in which they struggle to survive. The suffering is further presented to a larger audience through the film Valiya Chirakulla Pakshikal (2015, Dir. Dr Biju) by assimilating the reel and the real to bear testimony to their struggles amidst the toxicity of the chemical. The film, as the paper argues, becomes a representative text in the eco-trauma genre that on the one hand displays the disaster while on the other offers a cultural resistance against the unchecked use of chemicals around us. The film situates the Endosulfan disaster amongst the global movements against the pesticides and emphasises the need of a healthy environment.